HUBUNGAN PENGETAHUAN DAN SIKAP BIDAN DENGAN PENGGUNAAN APD DI RSUD EMBUNG FATIMAH - Friskan Afriani Panjaitan; Silvia Mona (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2017)
The use of PPD is regulated as a self-protector as well as an effort to reduce the risks of occupational injury that one might experience at work. Based on the initial study conducted, it is found that 6 midwives followed the PPE procedure, on the other hand, 4 midwives did not. Thus, in this study, the researchers aim to determine the correlation of midwives’ knowledge levels and attitude in the using of the PPE while working, particularly midwives at Embung Fatimah District Hospital in 2017. This study was designed as an analytic survey research with cross sectional approach. As the data instrument, the questionnaires were utilized and distributed to 32 midwives as the respondents through total sampling technique. This study was conducted from May to September 2017. Further, the data gathered from the questionnaires was analyzed using Chi Square statistical test. The result of the study reveals that 32 midwives (71.9%) have good-knowledge level on PPE, beside 78.1% have positive attitude on PPE, and 59.4% obey the PPE regulation. Conversely, this finding notes a correlation of knowledge levels (p = 0.01) and attitude (p = 0.01) to the PPE use. Therefore, it can be concluded that there is a significant correlation between midwives’ knowledge levels and their attitude to the use of the PPE as the self-protection during labor in Embung Fatimah District Hospital in 2017. Furthermore, it is suggested to health and medical personnel to be able to apply Standard Operating Procedures (SOP) including the PPE in their working life.